DYNAMIC: Dynamic glucose management strategies delivered through a structured education program improves time in range in a socioeconomically deprived cohort of children and young people with type 1 diabetes with a history of hypoglycemia. Issue 2 (15th January 2021) - Pemberton, John S; Kershaw, Melanie; Dias, Renuka; Idkowiak, Jan; Mohamed, Zainab; Saraff, Vrinda; Barrett, Timothy G; Krone, Ruth; Uday, Suma
Abstract: Objectives: Create and evaluate the effectiveness of a structured education program in children and young people (CYP) with type 1 diabetes using continuous glucose monitoring (CGM). Design and methods: Step 1: CGM devices were evaluated for predetermined criteria using a composite score. Step 2: The education program was developed following review of international structured education guidance, dynamic glucose management (DynamicGM) literature, award‐winning diabetes educators' websites, and CGM user feedback. Step 3: Program effectiveness was assessed at six months by change in time below range (TBR) (<3.9mmol/L), time in range (TIR) (3.9‐10.0mmol/L), time above range level 2 (TAR2) (>13.9mmol/L), severe hypoglycemia and HbA1c using a paired T‐test. A DynamicGM score was developed to assess proactive glucose management. Factors predicting TBR and TIR were assessed using regression analysis. Results: Dexcom G6 was chosen for integrated CGM (iCGM) status and highest composite score (29/30). Progressive DynamicGM strategies were taught through five sessions delivered over two months. Fifty CYP (23 male) with a mean (±SD) age and diabetes duration of 10.2 (±4.8) and 5.2 (±3.7) years respectively, who completed the education program were prospectively evaluated. Evaluation at six months showed a significant reduction in TBR (10.4% to 2.1%, p <.001), TAR2 (14.1% to 7.3%, p <.001), HbA1c [7.4 to 7.1% (57.7 to 53.8 mmol/mol), p <.001] and severe hypoglycemic episodes (10 to 1, p <.05); TIR increased (47.4% to 57.0%, p <.001). Number of Dexcom followers ( p <.05) predicted reduction in TBR and DynamicGM score ( p <.001) predicted increased TIR. Conclusion: Teaching DynamicGM strategies successfully improves TIR and reduces hypoglycemia.